Medicare Advantage Prior Authorization Requirements for Otolaryngologic Procedures in 2021 - Miller, Lauren E.; Miller, Ashley L.; Rocco, James W.; Rathi, Vinay K. (Otolaryngology-head and neck surgery, 2024)
Little is known about the extent of prior authorization requirements in otolaryngology. We performed a secondary analysis of data comparing prior authorization (PA) policies across 5 major Medicare Advantage insurers to estimate the counterfactual proportion of 2021 Medicare Part B fee‐for‐service spending and utilization for commonly performed otolaryngologic procedures that would have required PA. The counterfactual proportion of spending (range: 20.4%–27.6%) and utilization (range: 1.8%–4.5%) requiring PA was relatively consistent across insurers and largely attributable to rhinologic procedures. However, PA requirements for specific services varied widely among insurers. Among the 70 (of 196; 35.7%) services subject to PA by any insurer, nearly half were subject to PA by a single insurer (n = 34; 48.6%). Only 10 (14.3%) services were subject to PA by 4 (n = 6; 8.6%) or 5 (n = 4; 5.7%) insurers. These discrepancies illustrate the challenges of navigating discordant insurer policies for otolaryngologists and raise concerns about the validity of certain PA requirements.